Upaya Non Penal dalam Pengawasan Peredaran Minuman Keras Tradisional (Studi Pada Negeri Seith Kecamatan Lehitu, Kabupaten Maluku Tengah) - Rani Fajri Lalihun; Remon Supusepa; Margie Gladies Sopacua (Faculty of Law, Universitas Pattimura, 2021)
Introduction: Social life in society always wants a change that can provide positive values in order to create harmony and peace in a social environment. The widespread use of alcohol in the community is not only consumed by adults in general but also for students.Purposes of the Research: Analyze and discuss non-penal efforts in overcoming the circulation of traditional drinks in Leihitu District, Central Maluku Regency.Methods of the Research: This research is descriptive analysis using an empirical juridical approach formulated in the results of library research and the data obtained will be analyzed and studied in a structured research system so that the results are obtained. Conclusions and suggestions will be drawn.Results of the Research: Consuming traditional liquor among the people of the country of the Peninsula, both students and adults often have an impact on things that are not good which can be said to be (internal community conflict) so that these events or incidents greatly affect the harmony and peace of people in this country in particular. The habit of consuming alcohol in excess so that it causes loss of control over oneself, or is often said to be drunk, which in turn gives birth to violations or even criminal acts that are very disturbing to society. As for non-penal efforts in the context of tackling the crime of distribution of traditional liquor in Leihitu sub-district, namely as follows: Supervision, socialization and control of alcoholic beverages involving religious leaders, the community, as well as the police.